Representasi Ketidakpercayaan terhadap Aparat dalam Media Visual Tragedi Kanjuruhan Malang - Hasanah, Ummi; Rifa'i, Muhamad Husain; Al Anshory, Abdul Muntaqim (Universitas Gadjah Mada, 2026)
The Kanjuruhan Tragedy, which occurred on October 2022 is recorded as one of the biggest football tragedies in the world, right after the Estadio Nacional Tragedy in Peru on May 1964, which claimed 328 lives. One of the main causes of both tragedies was the use of tear gas inside football stadiums, which is actually prohibited by FIFA regulations. This incident triggered a public distrust of the police, who were supposed to ensure security but instead of worsened the situation. This study aims to analyze the signs on media visuals related to the Kanjuruhan Tragedy, which represent public distrust of the police, and to explore the implied meanings that cannot be explicitly displayed on these media visuals. In addition, the study also examines actions that reflect the loss of trust in the authorities. The analytical approach used is Charles Sanders Peirce's semiotics, which includes the analysis of signs, objects, and interpretants. The analysis reveals that Kanjuruhan Tragedy media visuals convey public distrust toward the police, caused by negligence in carrying out their duties. This distrust is depicted through visual elements in the media visuals. Furthermore, the study also uncovers actions taken by the public in response to the loss of trust in the authorities.